An enhanced model for stochastic coordination - Oliveira, Nuno Ernesto Salgado (2016)
Publicado em "Proceedings of the First International Workshop on Formal Methods for and on the Cloud, iFMCloud@IFM 2016, Reykjavik, Iceland, 4th June 2016"